Origin of the large electrostrain in BiFeO3-BaTiO3 based lead-free ceramics. Issue 37 (5th September 2019) - Wang, Ge; Fan, Zhongming; Murakami, Shunsuke; Lu, Zhilun; Hall, David A.; Sinclair, Derek C.; Feteira, Antonio; Tan, Xiaoli; Jones, Jacob L.; Kleppe, Annette K.; Wang, Dawei; Reaney, Ian M.
Abstract : The large electrostrain (1 − x )BiFeO3 -0.3BaTiO3 - x Nd(Li0.5 Nb0.5 )O3 ceramics is explained by the presence of polar nano-regions which distort in the direction of the applied field within multiple local symmetries. Abstract : High electrostrain and breakdown strength (1 − x )BiFeO3 -0.3BaTiO3 - x Nd(Li0.5 Nb0.5 )O3 (BF-BT- x NLN) ceramics were studied by in situ synchrotron X-ray diffraction (XRD) in combination with Rietveld refinement and conventional transmission electron microscopy. At zero field, compositions transformed from majority ferroelectric rhombohedral to pseudocubic as the NLN concentration increased, with 0.27% strain achieved at 60 kV cm −1 for x = 0.01. The large measured macroscopic strain was commensurate with peak shifting in XRD peak profiles, yielding 0.6% total strain at 150 kV cm −1 . Strain anisotropy of ε 200 > ε 220 > ε 111 was observed but despite the large applied field, no peak splitting was detected. We therefore concluded that the large electrostrain is not achieved through a conventional relaxor to field induced long-range ferroelectric transition. Instead, the data supports a model where local polar regions distort in the direction of the applied field within multiple local symmetries (pseudosymmetry) without long range correlation. We proposed that pseudosymmetry is maintained in BF-BT- x NLN even at high field (150 kV cm −1 ) due to the large ion radii mismatch and competing ionic/covalent bonding between Ba 2+ and Bi 3+ ions.